The Application of Translation Strategies to Cope With Equivalence Problems in Translating Texts - Dhini Aulia (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2012)
Translation is a process to render the meaning from the source text into the target text. A translator, however, will find some problems during translation process. Equivalence is the case which often appears (i.e. culture specific concept, the source-language concept is not lexicalized in the target language, source-language word is semantically complex, etc). To cope with equivalnce problems in translation process, some experts suggest some strategies which can be applied in doing translation. Some strategies are transference, naturalization, cultural equivalent, etc. The strategies which often appears in the example texts in this paper are transference, naturalization, descriptive equivalent, couplet and  through-translation. It is recomended that translator apply the strategies if only there is no equivalence problem in target language.